The Cosmic Descent of Falling Angles: Ethiopian Orthodox Teachings, Astronomical Insights, and Philosophical Reflections - Belay Sitotaw Goshu; Muhammad Ridwan (Matondang Journal, 2025)
Religion, astronomy, and philosophy are just a few fields of human thought that have understood falling as a physical phenomenon and a symbolic idea. In the Ethiopian Orthodox tradition, falling is often viewed as a moral and spiritual descent, particularly in the narrative of the Book of Enoch, where the fall of angels represents disobedience and the corruption of humanity. Astronomically, falling is understood as the entry of meteors or meteorites into Earth’s atmosphere, governed by the laws of physics. Philosophically, falling is explored as a metaphor for existential struggles, with thinkers such as Plato, Sartre, and Nietzsche associating it with ignorance, despair, and the search for meaning. The objective is to examine the similarities and differences between the philosophical, astronomical, and theological perspectives on falling. The research adopts a qualitative methodology involving a thematic analysis of religious texts, scientific literature, and philosophical works. The findings reveal that while religious perspectives focus on the moral and spiritual aspects of falling, astronomical explanations offer a scientific understanding based on physical laws, and philosophical views use falling as a metaphor for human existential challenges. The study concludes a varied consideration of falling by providing insights from multiple intellectual traditions. The study recommends fostering interdisciplinary research to explore these views further, integrating spiritual and scientific perspectives, and promoting public education that bridges religious and scientific interpretations.